Transformation of Numeracy Learning through Ethnoliteration Approach and Deep Learning Strategies in the Society 5.0 Era - Dwiyani, Eryka; Nursalim, Mochamad; Puspita, Ari Metalin Ika (Papanda Publisher, 2025)
This research aims to develop and test the effectiveness of ethnoliteracy-based numeracy learning tools that are integrated with deep learning strategies in a pedagogical context in the context of multicultural elementary schools in Nganjuk Regency. Using the ADDIE model Research and Development (R&D) approach, the research was conducted in three schools with different local cultural backgrounds. Data was collected through participatory observation, in-depth interviews, numeracy tests, and document analysis. The results of the study showed that the learning tools developed were able to improve students' understanding of numeracy concepts with an average score increase of 24.3 points. In addition, there was an increase in positive attitudes towards mathematics, with a decrease in boredom from 42% to 12%, as well as an increase in metacognition scores from 2.3 to 3.9 (on a scale of 5). Contextualizing material through local culture has been shown to increase the relevance of student learning and engagement, which is reflected in the 96% attendance rate and the number of critical questions students ask. Despite obstacles such as limited learning resources and digital access constraints, the adaptation of teachers and students is able to overcome these challenges effectively. This study concludes that the integration of ethnoliteracy and pedagogical deep learning strategies significantly improves students' cognitive, affective, and participatory aspects in numeracy learning. The implication of these findings is the need to develop contextual learning based on local culture to improve the quality of numeracy education in multicultural primary schools.